2014
DOI: 10.1089/ars.2013.5668
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-Induced DNA Damage, Response, and Repair

Abstract: By utilizing the strategies outlined above, it may be possible to exploit differences between tumor and somatic cell DRR pathways, specifically their DSB repair mechanisms, to improve the therapeutic ratio of IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
261
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(289 citation statements)
references
References 86 publications
5
261
0
Order By: Relevance
“…Ionizing radiation interacts directly with DNA, producing double-strand breaks, but also produces chemical changes in DNA through the production of water-derived free radicals also known as reactive oxygen species 13 . As secondary events, reactive oxygen species interact with DNA through a variety of mechanisms, producing base damage, crosslinking and single strand breaks [13][14][15] .…”
Section: Rowmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionizing radiation interacts directly with DNA, producing double-strand breaks, but also produces chemical changes in DNA through the production of water-derived free radicals also known as reactive oxygen species 13 . As secondary events, reactive oxygen species interact with DNA through a variety of mechanisms, producing base damage, crosslinking and single strand breaks [13][14][15] .…”
Section: Rowmentioning
confidence: 99%
“…As secondary events, reactive oxygen species interact with DNA through a variety of mechanisms, producing base damage, crosslinking and single strand breaks [13][14][15] . The relative diversity of free radicals and molecular interactions induced by IR may help to explain the complexity of IR-associated mutational signatures, why multiple signatures are present in IR-induced malignancies, and why some of these signatures may be present in malignancies produced by other non-IR mutagens.…”
Section: Rowmentioning
confidence: 99%
“…Whether the KD and/or caloric restriction reduces the formation of RNS is as yet unknown. In fact, the main effect of the KD or CR may not be in altering the amount of radiation-induced damage, but may in fact be in modulating the ability of tumor and normal cells to repair radiation-induced damage (Klement and Champ 2014;Santivasi and Xia 2014). Studies have shown that caloric restriction can enhance DNA repair in normal cells (Heydari et al 2007); however, this may not be the case in tumor cells, and the differential response of tumor cells and normal cells to genotoxic stress may be mediated by reduced IGF1 and glucose in the tumor cells.…”
Section: Kd As An Adjuvant Therapymentioning
confidence: 99%
“…They are also induced by exogenous DNA damaging agents such as ionizing radiation [4], radiomimetic drugs [5], and oxidative stress [6]. The repair of these lesions is essential in order to maintain cellular homeostasis and genomic integrity, and a failure to do so causes chromosome loss or rearrangements contributing toward tumorigenesis and cell death.…”
Section: Introductionmentioning
confidence: 99%